Occurrence and behavior of Bacillus cereus in naturally contaminated ricotta salata cheese during refrigerated storage. (September 2016) - Spanu, Carlo; Scarano, Christian; Spanu, Vincenzo; Pala, Carlo; Casti, Daniele; Lamon, Sonia; Cossu, Francesca; Ibba, Michela; Nieddu, Gavino; De Santis, Enrico P.L.
Abstract: The present study shows the fate of Bacillus cereus in refrigerated ricotta salata cheese during shelf-life. 144 ricotta salata cheese belonging to nine naturally contaminated batches were stored refrigerated and analyzed at 24 h, 30, 60 and 90 days of storage. Total bacterial count, B. cereus spores and vegetative forms, intrinsic properties and composition were determined. The presence of spores was sporadic while the prevalence and the level of B. cereus vegetative cells decreased respectively from 83.3 % to 4.65 ± 0.74 cfu g −1 at the beginning of the observation period to 33.3 % and 1.99 ± 0.55 cfu g −1 after 90 days. No information is currently available on the fate of B. cereus in ricotta salata. The production process of ricotta salata includes steps such as whey heating followed by slow cooling of clots, which expose to the risk of spore germination and successive growth to levels compatible with toxins production. The prolonged refrigerated storage was not favorable to sporulation, explaining the successive death of vegetative cells. The present study demonstrate the potential risk of food poisoning as consequence of pre-formed emetic toxins in ricotta salata. Food safety of ricotta salata relies on the rapid refrigeration of the product during critical phases for cereulide production. Highlights: The study investigate a case of Bacillus cereus natural contamination in ricotta salata. The evolution of B. cereus contamination was assessed during refrigerated storage. Contamination was linked with raw milk quality during out of season sheep's milking. Refrigeration temperature inhibited sporulation of vegetative cells.